An in vitro Prosthodontics Study on the Impact of Mouth rinses on the Color Stability of Monolithic and Multilayered Yttria –Stabilized Zirconia - Sireen Meheshi; Milad Eshah; Mohamed Zeglam; Saleha Alalwani (Khalij-Libya Journal of Dental and Medical Research, 2024)
The diverse array of restorative materials utilized in computer-aided design/computer-aided manufacturing (CAD/CAM) technology necessitates a comprehensive understanding of their aesthetic properties and color stability. This study aimed to evaluate the color stability of two different types of zirconia after immersion in Chlorhexidine and ANTIPLACA mouthwashes. We prepared 30 zirconia specimens (n = 15) as follows: Group 1 consisted of monolithic zirconia and group 2 consisted of KATANA™ YML Zirconia. Groups 1 and 2 were divided into three subgroups (n = 5). Each subgroup was immersed in one of the following three solutions: distilled water (control), CHX, or ANTIPLACA 0%Alcohol. We recorded the samples’ color values at baseline and after immersion according to the CIELab system by using a color spectrophotometer operated by an experienced operator. All data were collected and analyzed using Graph Pad Instat (Graph Pad, Inc.) software for windows. Irrespective of group totally it was found that immersion solutions significantly affected on mean values as revealed by two-way ANOVA test (p=<0.0001< 0.05) where (0% Alcohol > CHX ≥ DW). Mouthwashes staining had a marked effect on the color of the tested zirconia materials. The color change was material and staining solution-dependent, with Monolithic Zirconia showing the greatest color stability. تتطلب المجموعة المتنوعة من المواد الترميمية المستخدمة في تقنية التصميم بمساعدة الكمبيوتر/التصنيع بمساعدة الكمبيوتر فهمًا شاملاً لخصائصها الجمالية واستقرار اللون. هدفت هذه الدراسة إلى تقييم استقرار اللون لنوعين مختلفين من الزركونيا بعد الغمر في غسولات الفم الكلورهيكسيدين وANTIPLACA. قمنا بإعداد 30 عينة من الزركونيا (ن = 15) على النحو التالي: تتكون المجموعة 1 من الزركونيا المتجانسة وتتكون المجموعة 2 من الزركونيا KATANA™ YML. تم تقسيم المجموعتين 1 و2 إلى ثلاث مجموعات فرعية (ن = 5). تم غمر كل مجموعة فرعية في أحد المحاليل الثلاثة التالية: الماء المقطر (التحكم)، أو CHX، أو ANTIPLACA 0% كحول. سجلنا قيم لون العينات في البداية وبعد الغمر وفقًا لنظام CIELab باستخدام مطياف الألوان الذي يديره مشغل ذو خبرة. تم جمع جميع البيانات وتحليلها باستخدام برنامج Graph Pad Instat (Graph Pad, Inc.) لنظام التشغيل Windows. وبغض النظر عن المجموعة الكلية، فقد وجد أن حلول الغمر أثرت بشكل كبير على القيم المتوسطة كما كشف عنها اختبار تحليل التباين ثنائي الاتجاه (p = <0.0001 <0.05) حيث (0% كحول > CHX ≥ DW). كان لصبغة غسول الفم تأثير ملحوظ على لون مواد الزركونيا المختبرة. كان تغير اللون معتمدًا على المادة ومحلول الصبغ، حيث أظهرت الزركونيا الأحادية أكبر قدر من ثبات اللون